Imprisoned But Innocent: wrongful Convictions and Imprisonments in Germany, 1990-2016 - Leuschner, Fredericke (Crime & delinquency, 2020)
Although in the United States wrongful convictions and imprisonments are a major public and scientific concern, this topic has been largely ignored in Germany for decades. The present article offers for the first time an overview of all accessible German cases of successful retrials involving convicted persons who served a prison sentence since 1990. The data refer to 31 wrongfully convicted persons in 29 independent cases. Although the largest group consists of cases of false allegations, some of the wrongly convicted were considered not guilty by reason of insanity, and a few wrongful convictions occurred because of eyewitness misidentification and false confessions. In addition, incorrect expert testimony contributed considerably to the wrongful conviction in some cases.